The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1678-91992010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory evaluation of juvenile rats experimentally envenomed with Tityus serrulatus venom

Abstract: Accidental envenomation caused by Tityus serrulatus scorpions is very common in Brazil and may result in serious cardiorespiratory alterations that are frequently fatal to children. In the present study, the effects of T. serrulatus venom on the cardiorespiratory system of recently weaned male Wistar rats were evaluated. Fifteen animals were distributed into three groups (n = 5). The control group A received 400 μL ultrapure water by subcutaneous injection, while the experimental groups B and C were injected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The precise reasons for this age-related difference in toxicity remain unclear, although possible explanations include a greater venom dose/body weight ratio in children compared to adults and age-related variations in sensitivity to the venom. Although experimental studies have also found differences in the lethality, cardiorespiratory responses and pharmacokinetics of T. serrulatus venom in young compared to adult rats (Nunan et al, 2001(Nunan et al, , 2003(Nunan et al, , 2004Pinto et al, 2010), the relevance of these findings to envenomation in humans is uncertain. The marked difference in the severity of envenomation (and lethality) between T. serrulatus and T. bahiensis in humans contrasts with the lack of significant differences in the lethality of venoms from these two species in standard LD 50 tests in laboratory animals (Bücherl, 1953;Nishikawa et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The precise reasons for this age-related difference in toxicity remain unclear, although possible explanations include a greater venom dose/body weight ratio in children compared to adults and age-related variations in sensitivity to the venom. Although experimental studies have also found differences in the lethality, cardiorespiratory responses and pharmacokinetics of T. serrulatus venom in young compared to adult rats (Nunan et al, 2001(Nunan et al, , 2003(Nunan et al, , 2004Pinto et al, 2010), the relevance of these findings to envenomation in humans is uncertain. The marked difference in the severity of envenomation (and lethality) between T. serrulatus and T. bahiensis in humans contrasts with the lack of significant differences in the lethality of venoms from these two species in standard LD 50 tests in laboratory animals (Bücherl, 1953;Nishikawa et al, 1994).…”
Section: Discussionmentioning
confidence: 99%